Pengaruh Harga Dan Lokasi Terhadap Keputusan Pembelian Pada Sultan Coffee - Bangun Rara’; Isak Pasulu; Dwibin Kannapadang (Jurnal Ekonomi Bisnis dan Akuntansi, 2023)
The research method used in this study is quantitative research with a sample of 70 Sultan Coffee consumers. The data analysis technique used in this study is a multiple linear regression test using SPSS version 25.0 The results of this study show that partially price variables have a significant effect on purchasing decisions, location variables have a significant effect on purchasing decisions. Price and location variables simultaneously influence the purchase decision at Sultan Coffee